Conceptual Reconstruction of Money in Islamic Economics: A Comparative Analysis of Classical and Contemporary Literature - Eka Saputra; Wargo; Daud (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to reconstruct the conceptual framework of money in Islamic economics through a comparative analysis of classical and contemporary literature. This study employs a qualitative approach using a library research method, analyzing classical works of prominent scholars such as Al-Ghazali and Ibn Khaldun, alongside contemporary contributions from modern Islamic economists. The data are examined through descriptive-analytical and comparative techniques to identify continuity, divergence, and transformation in the conceptualization of money. The findings reveal that both classical and modern Islamic scholars consistently reject the commodification of money and emphasize its functional role in facilitating real economic activities. Classical literature highlights moral restrictions, including the prohibition of riba, hoarding (ikhtikar), and speculative practices, while modern literature extends these principles into discussions on monetary reform, financial instruments, and alignment with maqasid al-shariah. This study contributes by offering a conceptual synthesis that bridges classical foundations with contemporary economic challenges, providing a more integrated theoretical framework for Islamic monetary thought. The implications suggest the need for reorientation of modern financial systems toward ethical, justice-oriented, and stability-driven principles as advocated in Islamic economics